Strategi Guru dalam Implementasi Kurikulum Merdeka di SMA Muhammadiyah 8 Palembang - Yunniarti Yunniarti; Tri Widayatsih; Nuril Furkan (Journal on Education, 2025)
Teachers as the frontline in the implementation of the independent curriculum certainly have a strategy so that the curriculum of merdeka has an impact on strengthening student knowledge and character formation of students so that this study aims to describe and analyze teacher strategies in planning learning, implementing learning, assessing the learning process, teacher obstacles in implementing the curriculum of merdeka, and solutions carried out by teachers in implementing the curriculum of merdeka. Data collection used interview, observation and document techniques. Data were analyzed using interactive model analysis techniques. The results of the study concluded 1) teacher strategies in planning learning, namely: understanding the substance of the curriculum of merdeka, analyzing student needs, determining learning objectives, choosing learning methods and media, designing learning activities according to student needs; 2) teacher strategies in implementing learning, namely differentiated learning, fostering critical and creative thinking, cognitive and non-cognitive formative assessments, constructive feedback and a learning environment for active participation, involving students in the Pancasila profile strengthening project; 3) teacher strategies in assessing the learning process, namely: compiling assessment criteria, determining assessment methods, compiling assessment instruments according to student needs, implementing assessments, follow-up plans for assessment results; 4) obstacles faced by teachers, namely lack of understanding of the curriculum of merdeka, limited resources and facilities, changes in learning methods, high administrative burden; 5) solutions to overcome obstacles, namely: being active in learning communities, utilizing educational resources, utilizing technology for learning administration, mentoring and assistance, collaboration in discussing and reflecting on learning problems, internal platforms for sharing experiences and best practices between teachers.